Kinerja Guru Bimbingan Dan Konseling Pada Sekolah Menengah Atas Di Aceh Besar - Syaiful Bahri; Nurhasanah Nurhasanah; Muhammad Sauqi (Fakultas Dakwah dan Komunikasi Universitas Islam Negeri Sultan Syarif Kasim Riau, 2022)
The purpose of this research is to know the performance description of guidance and counseling teachers at high schools in Aceh Besar and what factors influence the performance of guidance and counseling teachers at high schools. This research uses a quantitative descriptive approach with a population and research sample of 27 counseling teachers spread across 19 schools. Techniques for data collection using a scale 4 questionnaire and data analysis techniques using descriptive analysis. The results of the study show that (1) the performance description of Guidance and Counseling Teachers at SMA is in the moderate category (Less Professional) with a frequency of 19 people (70%). (2) the results of the analysis of the factors that affect the performance of guidance and counseling teachers are divided into two, namely (a) Internal factors with high gains and a frequency of 21 people (78%) this is caused by the health condition of the Counseling Teachers, (b) External factors are in the high category and the frequency is 20 people (74%) this is due to the principal's leadership style. Based on the results of this analysis, the good or bad performance of the counseling teacher is greatly influenced by the health condition of the counseling teacher and the leadership style of the school principal.